Nutrición de la Playa de Matinhos y Complejidad de la Gestión Costera: Cooperación entre la Universidad y la Fiscalía - Silveira Miura, Aika; da Mata Cavalcante, Priscila; Lloret, Jaime (Costas, 2023)
The Paraná State Prosecutor’s Office launched an investigation against the Paraná State and its Environmental Agency due to serious illegalities in the bidding and licensing procedure of a project that cost around US 77,861,223.28, to contract a company for the execution of the work of Matinhos Seafront Recovery. Since the analysis of the project required deep technical and scientific knowledge, the Prosecutor’s Office had the support of the Federal University of Paraná (UFPR), which delivered several technical notes, pointing out the problems of the studies, the administrative procedures, and the projects. After a long attempt of trying to reach an extrajudicial agreement, the Prosecutor’s Office had no other option than to file a lawsuit against the Paraná State and the IAT (Water and Land Institute) to annul the Bidding Procedure No. 49/2021 and the environmental licensing protocols and permits, since the environmental licensing procedures are null, without the obligatory Environment Impact Assessment (EIA/RIMA) and before the preparation of the basic and executive projects. Furthermore, the projects were expensive and carried out immense cultural, social, and environmental impacts and significant modifications to the natural environment, its coastal dynamics, and the ecosystem services provided, losing natural habitats, and interfering with nutrient circulation. Due to a partnership between the Public Ministry of Paraná and the Federal University of Paraná, a class action still pending final judgment was drawn up to analyze and question fundamental technical points neglected in carrying out public works to nourish the beach, in Matinhos, on the coast of the Paraná State, Brazil. The study reviews technical notes presented by university researchers and highlights gaps in the project’s environmental licensing. Remote sensing was used to analyze the variability of the area after beach fattening.